Formulation and in vitro evaluation of a fast-disintegrating/sustained dual release bucoadhesive bilayer tablet of captopril for treatment of hypertension crises - Sahar Abbasi; Gholamhossein Yousefi; Ali Asghar Ansari; Soliman Mohammadi-Samani (Wolters Kluwer Medknow Publications, 2016)
Hypertension crisis is one of the main health problems and its effective treatment is of high importance. For this purpose, fast-disintegrating and sustained release formulations of captopril, as a drug of choice, were prepared using conventional mucoadhesive polymers hydroxypropyl methylcellulose (HPMC), sodium carboxymethyl cellulose (Na-CMC), hydroxypropyl cellulose (HPC), Carbopol 934 (CP934) and sodium alginate (Na-alg). The optimum sustained release formulations were selected based on mean dissolution time (MDT). The swellability and mucoadhesive properties of selected formulations were assessed and compared. A direct relationship between swelling and release rates/adhesiveness of sustained release formulations was observed. The results showed that formulations containing combination of CP934 and cellulose-based polymers had the highest swellability, sustainability and adhesion strength. These formulations prolonged drug release up to 8 h showing good fitness to Korsemeyer-Peppas model. Moreover, the adopted fast-disintegrating tablet could release up to 100% of drug within 3 min in oral pH. Finally, a dual fast-disintegrating/sustained release bucoadhesive bilayer tablet consisting of optimized formulations was prepared releasing 30% of the drug initially within 15 min and the remaining up to 8 h which could be considered as an appropriate formulation for the treatment of hypertension crises.